1997
DOI: 10.1111/j.1439-0396.1997.tb00753.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary xylose as an energy source for young pigs

Abstract: Summary Energy balances were compared in eight pigs (6–8 kg) fed 5% glucose or 10% D‐xylose added to a basal diet. In a carry‐over design, each pig received the glucose and 2 weeks later the xylose diet or vice versa. The basal diet consisted mainly of barley, corn, soya flour and skim milk powder. Pigs were fed 1.3 times the maintenance requirement for energy. Energy balances were measured after 4 days of adjustment to the diet and over a 7 day period. The rate of weight gain was similar between the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 9 publications
(16 reference statements)
3
18
2
Order By: Relevance
“…Contrary to the results of previous studies [ 9 , 43 ], dietary xylose concentration did not affect total tract digestibility of DM, GE, or CP in biologically relevant ways. Among all treatments and throughout the entire trial, the ATTD of DM ranged from 87.6–89.1% and diet DE was found to be slightly lower in the 2% treatment compared to the other three treatments.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Contrary to the results of previous studies [ 9 , 43 ], dietary xylose concentration did not affect total tract digestibility of DM, GE, or CP in biologically relevant ways. Among all treatments and throughout the entire trial, the ATTD of DM ranged from 87.6–89.1% and diet DE was found to be slightly lower in the 2% treatment compared to the other three treatments.…”
Section: Discussioncontrasting
confidence: 99%
“…This was the first indication that the efficiency of xylose utilization decreases proportionally as dietary xylose concentration increases. These value are comparable to previous studies in pigs which reported that 35–53% of absorbed xylose is excreted in the urine [ 9 , 43 , 44 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations